Impacts of Colored Light-Emitting Diode Illumination on the Reproductive Performance and Bioactive Constituents and the Molecular Mechanism of Hypothalamus Gland in Zi-geese - Manyu, Li; Xiuhua, Zhao; Guojun, Liu; Guixue, Zhang (Frontiers in Veterinary Science, 2022)
Goose is a seasonal breeding animal. Its reproduction is regulated by hypothalamus-pituitary- gonad axis and also affected by environmental factors such as light and location. Zi-goose is characterized with long egg-laying period and high egg-laying potential and belongs to the long-day type of seasonal breeding. In this study,using metabonomics analysis technology to explore the regulation mechanism of different lighting on reproductive performance of Zi-goose.1481 differential metabolites were screened out totally, in which 583 differential metabolites were coming from hypothalamus of Zi-goose, 196 differential metabolites were coming from pituitary of Zi-goose and 692 differential metabolites were coming from ovary of Zi-goose. Under red light condition for 12 h, expression of 433 differential metabolites were down-regulated and expression of 150 differential metabolites were up-regulated in hypothalamus of Zi-goose, expression of125 differential metabolites were down-regulated and expression of 71 differential metabolites were up-regulated in pituitary of Zi-goose, expression of 355 differential metabolites were down-regulated and expression of 337 differential metabolites were up-regulated in ovary of Zi-goose. 33 differential metabolites were closely associated with 1264 transcripts and 400 homologous genes of related enzymes in hypothalamus of Zi-goose. 15 differential metabolites were closely associated with 163 transcripts and 47 homologous genes of related enzymes in pituitary of Zi-goose. 55 differential metabolites were closely associated with 1255 transcripts and 360 homologous genes of related enzymes in ovary of Zi-goose.15, 3 and 186 pairs of metabolite_transcript co-expression were screened out in hypothalamus, pituitary and ovary of Zi-goose respectively, which responded significantly to changes in light conditions.It was confirmed that four metabolic pathways were closely related to light regulation of reproductive performance of Zi-goose, namely GnRH signaling pathway, prolactin signaling pathway, thyroid hormone synthesis and ovarian steroidogenesis.Typical differential metabolites of arachidonic acid, glucose-6-phosphate, progesterone, glutathione, oxidized glutathione, testosterone, deoxyepiandrosterone and their related protein genes would play an important role in light regulation of reproductive performance of Zi-goose.